The Winners' Choice: Sustainable Economic Strategies for Successful 21st Century Regions - Mark Partridge; Rose Olfert (European Regional Science Association (ERSA), 2011)
Throughout the second half of the 20th Century, urbanization, new technologies, rapid labor-saving productivity growth in primary industries, and improved highways combined to create large-scale rural-urban functionally integrated regions. These forces have raised the stakes for regions in their pursuit of economic development and growth, making successful regional policy even more important. Changes to the governance structures consistent with the increased interdependence within broad rural-urban regions will improve the region's competitiveness; adopting fad-based approaches and policies aimed at "picking winners" will be less fruitful. Going forward, continuing globalization and environmental sustainability have the potential to fundamentally reshape relative regional attractiveness.
Keywords: 330